2016
DOI: 10.3171/2015.9.spine139
|View full text |Cite
|
Sign up to set email alerts
|

Myelopathic signs and functional outcome following cervical decompression surgery: a proposed myelopathy scale

Abstract: OBJECTIVE Cervical spondylotic myelopathy (CSM) is the most common cause of spinal cord dysfunction in adults. In spite of this, the impact of the changes in myelopathic signs following cervical decompression surgery and their relationship to functional outcome measures remains unclear. The main goals of our study were to prospectively assess changes in myelopathic signs with a functional outcome scale (the modified Japanese Orthopaedic Association [mJOA] scale) foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…However, long-term clinical follow-up has revealed concerns related to the complications associated with this approach and the acceleration of degeneration of the adjacent segments, in addition to the reappearance of related symptoms and signs of cervical spondylosis [ 5 7 ]. Full-endoscopic spinal surgery not only avoids the deficiency of open surgery but also fully preserves the biomechanical stability of the spine [ 28 , 29 ]. However, patients and nonspecialists have little knowledge of modern spinal full-endoscopic surgery techniques, and they are reluctant to undertake full-endoscopic treatment at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term clinical follow-up has revealed concerns related to the complications associated with this approach and the acceleration of degeneration of the adjacent segments, in addition to the reappearance of related symptoms and signs of cervical spondylosis [ 5 7 ]. Full-endoscopic spinal surgery not only avoids the deficiency of open surgery but also fully preserves the biomechanical stability of the spine [ 28 , 29 ]. However, patients and nonspecialists have little knowledge of modern spinal full-endoscopic surgery techniques, and they are reluctant to undertake full-endoscopic treatment at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term clinical follow-up has revealed concerns related to the complications associated with this approach and the acceleration of degeneration of the adjacent segments, in addition to the reappearance of related symptoms and signs of cervical spondylosis [5][6][7] . Full-endoscopic spinal surgery not only avoids the de ciency of open surgery but also fully preserves the biomechanical stability of the spine [28,29] . However, patients and nonspecialists have little knowledge of modern spinal full-endoscopic surgery techniques, and they are reluctant to undertake full-endoscopic treatment at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, the long-term clinical follow-up found that the associated complications of approach and the acceleration of degeneration of adjacent segments were the clinical concerned, and the related symptoms and signs of cervical spondylosis appeared again [5][6][7] . The development of spinal full-endoscopy not only avoided the deficiency of open surgery, but also fully preserve the biomechanical stability of the spine [28,29] . However, patients and non-specialists have little knowledge of modern spine fullendoscopic techniques, they are reluctant to undergo full-endoscopic treatment at an early stage.…”
Section: Discussionmentioning
confidence: 99%